EFFECT OF RETURN ON ASSETS AND DEBT TO ASSETS RATIO ON EARNINGS MANAGEMENT - Saragih, Bagas Permana; Rambe, Muis Fauzi (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2022)
The purpose of this study was to examine and analyze the effect of Debt to Assets Ratio and Return On Assets on earnings management in automotive companies listed on the Indonesia Stock Exchange.The population used isautomotive companies listed on the Indonesia Stock Exchange, while the samples that meet the criteria are sixcompany. This research approach uses associative research. The analysis technique used is multiple linear regression analysis. The results show that the independent variables in this study have a simultaneous effect on earnings management and partially the Debt to Assets Ratio and Return On Assets variables have no and no significant effect on the management of automotive companies listed on the Indonesia Stock Exchange.